Oribatid mites (Arachnida: Oribatida) in Estonia: A commented checklist - Sammet, Kaarel; Varusk, Sirle; Vacht, Piret; Anslan, Sten; Kurina, Olavi (Zootaxa, 2026)
Although the first data on Estonian oribatid mites date back to 1859 with the work of A. E. Grube, the fauna has never been systematically revised since then. Data from all previous literature sources contain reliable records of 128 species, to which are added 172 new species records, based on 456 samples from different microhabitats from all parts of Estonia. The Estonian oribatid mite fauna has thus records of 300 species, which is a comparable number with the neighboring countries. Three new combinations and three new synonyms are proposed: Cymbaeremaeus venosus (Grube, 1859) comb. nov. et syn. nov. = Cymbaeremaeus cymba (Nicolet, 1855), Cepheus tricuspidatus (Grube, 1859) comb. nov. et syn. nov. = Cepheus latus (C. L. Koch, 1835), Oribatella quadricuspis (Grube, 1859) comb. nov. and Kaszabobates helveticus Mahunka & Mahunka-Papp, 2000 = Kaszabobates olbiopolitanus Sergienko, 1980 = syn. nov.